2021
DOI: 10.1111/cas.14938
|View full text |Cite
|
Sign up to set email alerts
|

Identification of PDHX as a metabolic target for esophageal squamous cell carcinoma

Abstract: The metabolism in tumors is reprogrammed to meet its energetic and substrate demands. However, this metabolic reprogramming creates metabolic vulnerabilities, providing new opportunities for cancer therapy. Metabolic vulnerability as a therapeutic target in esophageal squamous cell carcinoma (ESCC) has not been adequately clarified. Here, we identified pyruvate dehydrogenase (PDH) component X (PDHX) as a metabolically essential gene for the cell growth of ESCC. PDHX expression was required for the maintenance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
(128 reference statements)
0
6
0
Order By: Relevance
“…Loss of PDH activity or function signifies the cellular transition to the glycolytic state, where pyruvate is converted to lactate in cancer cells, inducing aerobic glycolysis. Thus, PDHX (and PDH complexes in general) effectively exert tumor-suppressive effects by maintaining normal metabolic homeostasis [ 75 ]. Eastlack et al found that miR-27b inhibited the expression of the PDH complex by targeting the 3'UTR of PDHX , resulting in specific metabolic dysregulation.…”
Section: Non-coding Rna and Breast Cancer Glucose Metabolismmentioning
confidence: 99%
“…Loss of PDH activity or function signifies the cellular transition to the glycolytic state, where pyruvate is converted to lactate in cancer cells, inducing aerobic glycolysis. Thus, PDHX (and PDH complexes in general) effectively exert tumor-suppressive effects by maintaining normal metabolic homeostasis [ 75 ]. Eastlack et al found that miR-27b inhibited the expression of the PDH complex by targeting the 3'UTR of PDHX , resulting in specific metabolic dysregulation.…”
Section: Non-coding Rna and Breast Cancer Glucose Metabolismmentioning
confidence: 99%
“…Results of our study clarify possible mechanisms of glutamine and glucose deprivations on the proliferation/surviving of ERN1 knockdown glioma cells through specific changes in the expression profile of genes encoding important enzymes of PDH complex (Babady et al 2007;Mathias et al 2014;Eastlack et al 2018;Yonashiro et al 2018;Jin et al 2016;Yetkin-Arik et al 2019;Cai et al 2020;Shin et al 2020;Inoue et al 2021;Zaher et al 2021).…”
Section: Discussionmentioning
confidence: 62%
“…We also showed that PDHX is resistant to glutamine deprivation and these results also agree well with its essential role in the functional activity of a PDH complex (Eastlack et al 2018). Recently, it was shown that PDHX is a metabolically essential gene for the cell growth because its expression is required for the maintenance of PDH activity and the production of ATP and its knock-down inhibited the proliferation of cancer cells and in vivo the tumor growth (Inoue et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small molecule PDH inhibitors have been proven effective in pre-clinical models. CPI-613, a PDH inhibitor has been shown to inhibit the proliferation of cancer stem cells (CSCs) in vitro and the growth of ESCC xenograft tumors in vivo [34].…”
Section: Pyruvate Dehydrogenasementioning
confidence: 99%